The role of libraries in the use of African-published journals in African universities - Alemna, A.A.; Chifwepa, V.; Rosenberg, D. (The International Information & Library Review, 2001)
Although journal collections in African universities have deteriorated over the last 15 years, many libraries have more recently bene¢ted from schemes donating journal titles or money to purchase journals from the West. Since 1994, a number of university libraries in Anglophone Africa have had access to titles published in the rest of Africa through the African Journals Distribution Programme (AJDP). This paper reports on the study carried out the use of the journals in two of the universities ˆ University of Ghana, Legon and University of Zambia, Lusaka.